IL-1β Promotes Corneal Epithelial Cell Migration by Increasing MMP-9 Expression through NF-κB- and AP-1-Dependent Pathways - Tseng, Hui-Ching; Lee, I-Ta; Lin, Chih-Chung; Chi, Pei-Ling; Cheng, Shin-Ei; Shih, Ruey-Horng; Hsiao, Li-Der; Yang, Chuen-Mao (PLOS ONE, 2013)
Interleukin-1β (IL-1β) plays a critical mediator in the pathogenesis of eye diseases. The implication of IL-1β in inflammatory responses has been shown to be mediated through up-regulation of inflammatory genes, including matrix metalloproteinase-9 (MMP-9). However, the detailed mechanisms of IL-1β-induced MMP-9 expression in Statens Seruminstitut Rabbit Corneal Cells (SIRCs) are largely unclear. Here, we demonstrated that in SIRCs, IL-1β induced MMP-9 promoter activity and mRNA expression associated with an increase in the secretion of pro-MMP-9. IL-1β-induced pro-MMP-9 expression and MMP-9 mRNA levels were attenuated by pretreatment with the inhibitor of MEK1/2 (U0126), JNK1/2 (SP600125), NF-κB (Bay11-7082), or AP-1 (Tanshinone IIA) and transfection with siRNA of p42 or JNK2. Moreover, IL-1β markedly stimulated p42/p44 MAPK and JNK1/2 phosphorylation in SIRCs. In addition, IL-1β also enhanced p42/p44 MAPK translocation from the cytosol into the nucleus. On the other hand, IL-1β induced c-Jun and c-Fos mRNA expression, c-Jun phosphorylation, and AP-1 promoter activity. NF-κB translocation, IκBα degradation, and NF-κB promoter activity were also enhanced by IL-1β. Pretreatment with U0126 or SP600125 inhibited IL-1β-induced AP-1 and NF-κB promoter activity, but not NF-κB translocation from the cytosol into the nucleus. Finally, we established that IL-1β could stimulate SIRCs migration via p42/p44 MAPK-, JNK1/2-, AP-1-, and NF-κB-dependent MMP-9 induction. These results suggested that NF-κB and AP-1 activated by JNK1/2 and p42/p44 MAPK cascade are involved in IL-1β-induced MMP-9 expression in SIRCs.